Saga (Adenanthera pavonina Linn) Seeds Milk As An Alternative Source Of Protein From Tree Species - Novia Dwitanti; Elisa Julianti; Latifah Hanum; Wulan Syahputri; batubara, Ridwanti (Talenta Publisher, 2020)
Saga seeds derived from saga (Adenanthera pavonina Linn) trees belongs to the family Fabaceae (Leguminosae-Mimosaceae), have potential as a source of protein. This research aims to obtain information about the potential of saga seeds milk as alternative milk based on processing and flavor enhancements. The method of testing saga seeds milk protein using the determination of N-Total by the Semi-Micro Kjeldahl method. The consumer preference level test is carried out with a hedonic test in the form of assessment based on the color, aroma, and taste parameters. The results of the saga seeds milk protein test results with the addition of 150 mL of water and cooking time for 10 minutes contain protein levels 1.19% ± 0.16. Organoleptic test results showed that saga seeds milk with the addition of 200 mL of water, cooked for 10 minutes with strawberry flavor had the highest score with an average color of 3.72 ± 0.94, aroma 3.96 ± 0.90 and taste 3, 96 ± 0.90.